2016
DOI: 10.4102/sajems.v19i4.1415
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents to transformational community engagement in South Africa

Abstract: Firms face increasing societal pressures to act responsibly towards stakeholders, and community engagement is a key element of this response. While Bowen, Newenham-Kahindi and Herremans (2010) have found that community engagement strategies fall into the transactional, transitional and transformational categories, more research is needed. Nineteen semi-structured interviews were conducted with CSR practitioners, community beneficiaries and external experts across three companies from different sectors and geog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Research on corporate engagement strategies continues to provide new insights on the confluence of business and society (Delannon et al 2018;Bowen et al 2010;Stirling et al 2016). Corporate engagement can lie anywhere on the continuum of community engagement of 'transactional', 'transitional' and 'transformative' (Bowen et al 2010), and empirical research has found that these corporate engagement strategies can vary from being 'passive', such as simply giving donations (Lorenz et al 2013), to being applied in a complementary approach -an 'integrational' strategy', consisting of elements of all three strategies (Delannon et al 2018, 719).…”
Section: Corporate Community Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on corporate engagement strategies continues to provide new insights on the confluence of business and society (Delannon et al 2018;Bowen et al 2010;Stirling et al 2016). Corporate engagement can lie anywhere on the continuum of community engagement of 'transactional', 'transitional' and 'transformative' (Bowen et al 2010), and empirical research has found that these corporate engagement strategies can vary from being 'passive', such as simply giving donations (Lorenz et al 2013), to being applied in a complementary approach -an 'integrational' strategy', consisting of elements of all three strategies (Delannon et al 2018, 719).…”
Section: Corporate Community Engagementmentioning
confidence: 99%
“…The relationship between business and its mosaic of stakeholders continues to occupy researchers' attention as they grapple to better understand the underlying factors that arbitrate these relationships. Dedicated engagement by companies with community stakeholders holds the promise to contribute to the well-being of communities, especially in countries with urgent development priorities (Stirling et al 2016). An effective corporate community engagement strategy has the propensity to build close relationships between companies and their communities (Liu et al 2013) and to generate civic wealth (Lumpkin and Bacq 2019), yet the benefits are not clearly understood which suggests further inquiry in this regard is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…It is true that ‘companies are increasingly aware that they are no longer accountable to shareholders alone’ (Stirling et al, 2016, p. 516) and a great deal of interesting work is being done in developing ways of working with a wider range of stakeholders than only those who have a direct financial stake in the company. Community engagement broadens the purpose of corporations not only in terms of serving a more diverse group of stakeholders but also in terms of expanding the time horizon – there is now less focus on short-term profit and more on the long-term impact that companies have in society (Ditlev-Simonsen, 2010).…”
Section: Corporatisationmentioning
confidence: 99%
“…As is the case with all academic and professional fashions, there is always, in the words of Stirling, Wilson-Prangley, Hamilton, and Olivier (2016), ‘the risk that engagement is symbolic rather than substantive’ (p. 514). Our hope is that by mapping the past, present, and future landscape within which community engagement flourishes, we will be able to highlight ways in which superficial, routinised engagement with communities can be avoided and meaningful, transformative cooperation fostered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation